Direct to operating room trauma resuscitation: Optimizing patient selection and time-critical outcomes when minutes count. Issue 1 (July 2020) - Johnson, Amelia; Rott, Michael; Kuchler, Andrea; Williams, Emma; Cole, Fredrick; Ramzy, Ameen; Barbosa, Ronald; Long, William; Martin, Matthew J.
Abstract : BACKGROUND: Although several trauma centers have developed direct to operating room (DOR) trauma resuscitation programs, there is little published data on optimal patient selection, practices, and outcomes. We sought to analyze triage criteria and interventions associated with optimal DOR outcomes and resource utilization. METHODS: Retrospective review of all adult DOR resuscitations for a 6-year period was performed. Triage criteria were analyzed individually and grouped into categories: mechanism, physiology, anatomy/injury, or other. The best univariate and multivariate predictors of requiring lifesaving interventions (LSIs) or emergent surgery (ES) were analyzed. Actual and predicted mortality were compared for all patients and for predefined time-sensitive subgroups. RESULTS: There were 628 DOR patients (5% of all admissions) identified; the majority were male (79%), penetrating mechanism (70%), severely injured (40% ISS >15), and 17% died. Half of patients required LSI and 23% required ES, with significantly greater need for ES and lower need for LSI after penetrating versus blunt injury ( p < 0.01). Although injury mechanism criteria triggered most DOR cases and best predicted need for ES, the physiology and anatomy/injury criteria were associated with greater need for LSI and mortality. Observed mortality was significantly lower than predicted mortality with DOR for several key subgroups. Triage schemes for both ES and LSI could be simplified to four to six independent predictors by regression analysis. CONCLUSION: The DOR program identified severely injured trauma patients at increased risk for requiring LSI and/or ES. Different triage variable categories drive the need for ES versus LSI and could be simplified or optimized based on local needs or preferences. Direct to operating room was associated with better than expected survival among specific time-sensitive subgroups. LEVEL OF EVIDENCE: Therapeutic/Care Management, Level IV. Abstract : Supplemental digital content is available in the text.